Back analysis of a slope failure by using PLAXIS Code / Syahrul Rozaily Usul - Usul, Syahrul Rozaily (2004)
This final year project is related with the stability control of an embankment built on soft clay soils in Kg Paka, Terengganu. It consists of three parts; the first part is the data presentation of the actual failure of embankments on the PETRONAS gas processing plant. The data available are the observation of the failure pattern and the result of equilibrium method via Geoslope Software. The second part is the analysis of the failure by using Finite Element Method via PLAXIS Code. The simulation of the failure is governed by Mohr-Coulomb profile. The third part presents the comparison between the actual failure result and the PLAXIS Code; and between the Geoslope Software and PLAX1S Code. The comparison leads to the reliable and appropriateness of the finite element method (PLAXIS) usage.